2013
DOI: 10.1186/ar4407
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of soluble MER in lupus reflect M2c activation of monocytes/macrophages, autoantibody specificities and disease activity

Abstract: IntroductionSystemic lupus erythematosus (SLE) is characterized by impaired efferocytosis and aberrant activation of innate immunity. We asked if shedding of MER receptor tyrosine kinase (MerTK) and AXL into soluble (s) ectodomains was related to immunological and clinical aspects of SLE.MethodsLevels of sMER and sAXL in the plasma of 107 SLE patients and 45 matched controls were measured by ELISA. In 40 consecutive SLE patients, we examined potential correlations between either sMER or sAXL and plasma levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 53 publications
4
64
0
Order By: Relevance
“…Recent studies by Zizzo et al [25,69] suggested a strict correlation between systemic lupus erythematosus (SLE) disease severity and the activation of an M2-like macrophage characterized by CD163 and MerTK expression during the monocyte-to-macrophage differentiation. Expanding upon our previous observation that the monocyte compartment becomes perturbed in TB patients [18], we now report that the CD163 + MerTK + pSTAT3 + signature accompanies the expansion of the CD16 + monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Zizzo et al [25,69] suggested a strict correlation between systemic lupus erythematosus (SLE) disease severity and the activation of an M2-like macrophage characterized by CD163 and MerTK expression during the monocyte-to-macrophage differentiation. Expanding upon our previous observation that the monocyte compartment becomes perturbed in TB patients [18], we now report that the CD163 + MerTK + pSTAT3 + signature accompanies the expansion of the CD16 + monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of advanced atherosclerosis, this profound deficit promotes key features of clinically dangerous plaques, including necrosis, imbalance of proresolving versus proinflammatory lipid mediators, fibrous cap thinning, and deficiency of Tregs. The finding that cleavage of a single molecule in the setting of a chronic inflammatory condition could have such robust pathophysiologic effects not only suggests its potential as a therapeutic target but also raises the question of the possible role of MerTK cleavage in other chronic inflammatory conditions previously linked to MerTK and sol-Mer, e.g., systemic lupus erythematosus and Sjögren's syndrome (35)(36)(37)(38). …”
Section: Author Contributionsmentioning
confidence: 99%
“…This process disables MerTK, and the cleavage product, soluble Mer (sol-Mer), may competitively inhibit the interaction of intact MerTK with its ligands (21,22). Plasma solMer is increased in patients with active systemic lupus erythematosus and rheumatoid arthritis (23,24), and cell-surface MerTK is lower in macrophages in ADAM17-rich areas in advanced human atherosclerotic lesions (25). However, causation studies are lacking.…”
Section: -Lipoxygenasementioning
confidence: 99%